Combining Individual‐Based Radio‐Tracking With Whole‐Genome Sequencing Data Reveals Candidate for Genetic Basis of Partial Migration in a Songbird - Matthias H. Weissensteiner; Kira Delmore; Valentina Peona; Juan Sebastian Lugo Ramos; Gregoire Arnaud; Julio Blas; Bruno Faivre; Ivan Pokrovsky; Martin Wikelski; Jesko Partecke; Miriam Liedvogel (Ecology and Evolution)
ABSTRACT Partial migration is a phenomenon where migratory and resident individuals of the same species co‐exist within a population, and has been linked to both intrinsic (e.g., genetic) as well as environmental factors. Here we investigated the genomic architecture of partial migration in the common blackbird, a songbird that comprises resident populations in the southern distribution range, partial migratory populations in central Europe, and exclusively migratory populations in northern and eastern Europe. We generated whole‐genome sequencing data for 60 individuals, each of which was phenotyped for migratory behavior using radio‐telemetry tracking. These individuals were sampled across the species' distribution range, including resident populations (Spain and France), obligate migrants (Russia), and a partial migratory population with equal numbers of migratory and resident individuals in Germany. We estimated genetic differentiation (FST) of single‐nucleotide variants (SNVs) in 2.5 kb windows between all possible population and migratory phenotype combinations, and focused our characterization on birds from the partial migratory population in Germany. Despite overall low differentiation within the partial migratory German population, we identified several outlier regions with elevated differentiation on four distinct chromosomes. The region with the highest relative and absolute differentiation was located on chromosome 9, overlapping PER2, which has previously been shown to be involved in the control of the circadian rhythm across vertebrates. While this region showed high levels of differentiation, no fixed variant could be identified, supporting the notion that a complex phenotype such as migratory behavior is likely controlled by a large number of genetic loci.